Editorial - Oniwide, Oyetola (NIU Journal of Educational Research, 2024)
This issue of NIU Journal of Educational Research touches on Music Education, Environmental Education, Health Security Education, Technological Education in Curriculum Management, as well as Agricultural Education. One of the papers, in this issue, argues that music education cannot be achieved unless there are enough professionally trained, efficient, committed, and effective teachers. It is necessary to lay much emphasis on the training of music education teachers, products of which will be responsible for the implementation of the aims and objectives of music education programs in the pre-primary, primary, secondary, and tertiary institutions in Nigeria. Another paper also reveals that the educational system is witnessing digital transformation driven by technological advancement which seems promising. To keep pace with this novel phenomenon and benefit from the usage, management education needs to equip teachers with the knowledge and skills necessary to leverage this technological advancement through its integration in curriculum. This paper therefore examines the technology to be deployed to the classroom for effective management of students, its benefits, potential approaches and considerations for successful implementation. On the whole, this issue of NIU Journal of Educational Research features many empirical and theoretical based articles which can be of great benefit to every reader.